2023
DOI: 10.1186/s12891-023-06221-3
|View full text |Cite
|
Sign up to set email alerts
|

A novel modified McLaughlin surgery for treating locked chronic posterior shoulder dislocation

Abstract: Background Posterior shoulder dislocation is an uncommon orthopaedics injury and is frequently missed or misdiagnosed, accounting for 2%-4% of all shoulder dislocations, and is associated with the reverse Hill-Sachs lesion. Once posterior shoulder dislocation develops into a chronic disease, it will bring a lot of trouble to the treatment, especially in repairing the humeral defects. Surgical strategies are also developing and innovating to deal with this injury, including transfer of subscapul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…Post-operative weighted average flexion was 137.1 (107.1-157.7). Pre-operative abduction was reported only by 4 studies [28,[31][32][33]; the weighted average was 44.4 • (13.3-95); and the post-operative abduction weighted average was 136.6 (95.8-171.4).…”
Section: Overall Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Post-operative weighted average flexion was 137.1 (107.1-157.7). Pre-operative abduction was reported only by 4 studies [28,[31][32][33]; the weighted average was 44.4 • (13.3-95); and the post-operative abduction weighted average was 136.6 (95.8-171.4).…”
Section: Overall Resultsmentioning
confidence: 99%
“…Pre-operative weighted average external rotation with the adducted arm was 1.3 • (−6.7-8.3 • ) and post-operatively it increased to 45.4 • (35-79.2). Eight studies reported the external rotation range with the abducted arm and the average post-operative value was 72.2 • (51-83.6) [5,6,21,25,26,29,32,33]. Pre-operatively average weighted internal rotation was 9.4 • (1-25) and was reported in three studies [5,29,31].…”
Section: Overall Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…When treating PSD and reducing shoulder injuries, arthroscopic 10 is preferred over open 17 procedures due to their minimally invasive approach and the ability to visualize the articular surface and the posterior capsulolabral junction. This allows for better centering of the humeral head through direct visualization.…”
Section: Discussionmentioning
confidence: 99%